A Single-Center Case Series of Successful Abdominal Organ Transplantation From SARS-CoV-2–infected Donors to Uninfected Recipients—Do We Need Rigorous Monitoring?. Issue 4 (15th March 2023) - Singh, Priyamvada; Von Stein, Lauren; Doraiswamy, Mohankumar; Samidurai, Lakshmi; Singh, Navdeep; Maxwell, Molly; Pesavento, Todd E
Abstract : Background: There is limited documentation of hematogenous transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in non–lung transplants from infected donors to uninfected recipients. Methods: We analyzed 16 recipients (7 liver, 9 kidney) transplanted from SARS-CoV-2 nucleic acid test + deceased donors from December 25, 2021, to February 28, 2022, who were followed-up for at least 90 d. Primary outcomes included coronavirus disease 2019–positivity, allograft loss, and all-cause mortality. Secondary outcomes included biopsy-proven rejection (BPAR), donor-specific antibodies, delayed graft function, and opportunistic infections. Unlike previous studies, we followed the recipients clinically with the intent to treat if they developed SARS-CoV-2 symptoms. Results: All donors were SARS-CoV-2 polymerase chain reaction–positive 72 h before donation. No recipients developed SARS-CoV-2 infection. The nadir serum creatinine and estimated glomerular filtration rate were 1.33 mg/dL and 64 mL/min/1.732 m 2 for kidney transplantation (KTx) respectively. The median alanine transaminase was 14.5 IU/L, aspartate aminotransferase 13 IU/L, and alkaline phosphatase 74 IU/L. Two KTx patients lost allograft, and 1 liver transplantation patient died with a failed allograft. However, this was unrelated to their SARS-CoV-2–positive donor status. One BPAR in the liver transplantation was treated with steroids. No donor-specific antibodies or BPAR were reported in the KTx. Six KTx patients experienced delayed graft function, and 4 are off dialysis. Two KTx patients developed cytomegalovirus infection because of an error in reporting the cytomegalovirus serostatus by the donor center. We did not do serial testing for SARS-CoV-2 by polymerase chain reaction, imaging, or cycle threshold score pre- or posttransplant for donor/recipient and had comparable outcomes with previous studies. Conclusions: Because of the low risk of transmission, serial testing might not be necessary and, thus, could be reciprocated at small-volume transplant centers.